Acoustic modelling of surface sources. Part I. Piston model, discretizing error, axisymmetrical problem - BRAŃSKI, A. (Archives of Acoustics, 1995)
The paper discusses the application of irregular boundary elements in BEM method. These elements were proposed in order to reduce the number of the elements in acoustical model of surface source. The boundaries of irregular elements were introduced by optimizing a mean square distance between exact directivity function and approximation one. The constant vibration velocity on each element was calculated employing the definition of an average function value. For simplicity as an example radiation axisymmetric problem governed by Helmholtz-Rayleigh integral was considered. Examples are shown that applying irregular discretization better model may be obtained.